2010
DOI: 10.1021/ja100625p
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State115In and31P NMR Studies of Triarylphosphine Indium Trihalide Adducts

Abstract: Solid-state (115)In and (31)P NMR spectroscopy, relativistic density functional theory (DFT) calculations, and single-crystal X-ray diffraction were used to investigate a series of triarylphosphine indium(III) trihalide adducts, X(3)In(PR(3)) and X(3)In(PR(3))(2) (X = Cl, Br or I; PR(3) = triarylphosphine ligand). The electric field gradient tensors at indium as well as the indium and phosphorus magnetic shielding tensors and the direct and indirect (115)In-(31)P spin-spin coupling were characterized; for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 95 publications
7
42
0
Order By: Relevance
“…It is in fact possible to predict the required molecular properties (nuclear shieldings and couplings) to an accuracy that enables one to use such predictions for structure determination. This has been demonstrated for ''routine'' nuclei such as 1 H or 13 C [15][16][17][18] as well as for unusual heteronuclei as 99 Ru, 119 Sn, 183 W, 195 Pt, or 199 Hg (to mention just those for which fairly systematic studies have been carried out) [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is in fact possible to predict the required molecular properties (nuclear shieldings and couplings) to an accuracy that enables one to use such predictions for structure determination. This has been demonstrated for ''routine'' nuclei such as 1 H or 13 C [15][16][17][18] as well as for unusual heteronuclei as 99 Ru, 119 Sn, 183 W, 195 Pt, or 199 Hg (to mention just those for which fairly systematic studies have been carried out) [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 93%
“…Given the good performance of the ZORA-DFT framework in the prediction of NMR shifts for many heavy-atom nuclei such as 183 W, [19][20][21][22][23][24][25] we reckoned that the approach could be extended to heavier atoms as well. Given the expected difficulty of this problem, we calculated the shifts with the SAOP model functional in addition to BP86 and PBE0, since SAOP was reported to provide improved 183 W shieldings at a modest computational cost [109].…”
Section: Uranium Chlorofluoridesmentioning
confidence: 99%
“…Recently, Chen et al have shown the utility of 115 In SSNMR for studying indium coordination complexes in which the indium is in the +3 oxidation state, 22,41 and Bryce and coworkers have reported 115 In ultra-wideline NMR spectra of two In(I)bis(imino)pyridine analogues. 42 Herein, we describe the first detailed 115 In SSNMR study of low oxidation-state indium Static (i.e., stationary sample) NMR spectra were acquired at both moderate and ultra-high magnetic field strengths (9.4 and 21.1 T) in order to accurately measure the EFG and CS tensor parameters.…”
Section: Measurements Of the 115mentioning
confidence: 99%
“…The 115 In quadrupolar coupling constants, Cq( 115 In), range from AE 1.25 AE 0.10 to -166.0 AE 2.0 MHz. 221 A phase diagram for the antiferromagnetism and superconductivity in Ce 2 RhIn 8 probed by In-NQR studies under pressure (P) was reported. The quasi-two-dimensional character of antiferromagnetic spin fluctuations in the paramagnetic state at P = 0 evolves into a three-dimensional character because of the suppression of antiferromagnetic order for P W PQCP B 1.36 GPa (QCP: quantum critical point).…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%
“…The 115 In quadrupolar coupling constants, C(Q)( 115 In), range from þ /-1.25 þ /-0.10 to -166.0 þ /-2.0 MHz. 229 2.13.5 Thallium ( 203, 205 Tl)(I = 1/2, 1/2). Slow cooling of melts composed of TlCl and BiCl 3 allows for the isolation of the compounds Tl 3 BiCl 6 (1) and TlBi 2 Cl 7 (2).…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%